Land use changes of the Tihany Peninsula - Barczi, Attila; Grónás, Viktor; Nagy, Valéria (JOURNAL OF LANDSCAPE ECOLOGY, 2017)
The use of land adapted to natural conditions – with special regard to agriculture – has changed a lot in the last century. At the beginning of the century agricultural land use did not consider soil conditions: human intervention has significantly transformed the soils of Tihany Peninsula. In addition, the proportion of built-up areas has increased considerably, and soil degradation has been accelerated mainly in arable fields and vineyards. By declaring the protection of the peninsula, it became possible to create a more suitable farming activity to the ecological conditions of the area, which also means less agricultural use, and more attention to soil conditions. The nature conservation restored the water cover of the drained areas in accordance with the original ecological conditions and helped the reforestation, as well as manages dry grasslands. At present, the income of the population of the area is based on agriculture and tourism, but this latter activity also damages the protected values and the soils of the peninsula. Only the rocky grasslands, the Quercus pubescens shrubs and the restored bogs remained in their original natural state.
Keywords: Tihany Peninsula; landscape; land use